Experimental study on the effect of loading rate on the strain energy accumulation and release during the weakening process of circular-tunnel - Xun You; Yunmin Wang; Xiangxin Liu; Kui Zhao; Zhengnan Zhang (Geomechanics and Geophysics for Geo-Energy and Geo-Resources, 2024)
Abstract The weakening of circular tunnels is a global problem that has not been resolved satisfactorily. In the tunnelling process, surrounding rock of circular-tunnel performs a process of “excavating → weakening → continuous excavating → weakening strengthens”. Different rates of excavation affect the stress adjustment of the surrounding rock, and also have an impact on the weakening of a circular-tunnel. An instability failure test was conducted on a circular-tunnel with varying vertical loading rates. The loading rate was utilized as a representative measure for the excavation rate on the site. The results showed that the weakening process of a circular-tunnel can be divided into four distinct phases, hydrostatic pressure (E1), particle ejection (E2), flake stripping (E3), and instability (E4). The ordering of these phases is E3 > E4 > E1 > E2. In the weakening process of a circular-tunnel, the root cause is the original stress level, while the essential factor is the engineering disturbance. A faster vertical loading rate leads to greater stress adjustment, higher strain energy accumulation, and an increased probability of circular-tunnel instability. The presence of a quiet period of AE events in the middle and later phases of flake stripping is a precursory characteristic of circular-tunnel instability. This study has both theoretical and practical significance in terms of revealing the mechanism of circular-tunnel instability and achieving a reasonable arrangement of the circular-tunnel support process.